Prediksi Hasil Produksi Padi di Kabupaten Pamekasan Menggunakan Semi Average - Anis Fitriyah; Siti Khotijah (Alpha-Epsilon: Journal of Mathematics, 2026)
This study aims to predict the amount of rice production in Pamekasan Regency using the Semi Average method. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) of Pamekasan Regency, covering the observation period from 2015 to 2024. The analysis process began with processing historical rice production data using the method, followed by an evaluation of forecasting accuracy using the Mean Absolute Percentage Error (MAPE). The results of the analysis indicate that the Semi Average method produces a forecasting pattern with a MAPE value of 46.62%, which falls into the fair category based on MAPE interpretation, indicating a moderate level of accuracy. The results of this study are expected to serve as a reference for agricultural sector planning, particularly in managing sustainable rice production in Pamekasan Regency.